Blood lactate as a marker of exercise adaptation and fatigue in male mice with chronic heart failure - Ahmed M. Wafi; Lie Gao; Irving H. Zucker (Physiological Reports)
Abstract Treadmill exercise tests assess aerobic capacity in chronic heart failure (CHF) mice, but subjective exhaustion criteria limit reproducibility. Elevated blood lactate (La) at exhaustion may provide an objective fatigue marker. This study evaluated La at exhaustion and the effects of exercise training (ExT) on resting La in CHF mice. Sham and coronary artery ligation‐induced CHF mice were assigned to sedentary (Sed) or ExT groups. Blood La was measured from 0.7 μL tail vein samples at rest and at exhaustion during exercise tests after 8 weeks of ExT. Blood La at rest was slightly higher in CHF‐Sed mice (3.33 ± 1.23 mmol/L) than in Sham‐Sed mice (2.96 ± 0.42 mmol/L; p = 0.86). ExT slightly reduced La in CHF mice (2.55 ± 0.63 mmol/L; p = 0.34 vs. CHF‐Sed), but differences were not significant. At exhaustion, blood La increased significantly across groups. Baseline La in CHF‐Sed mice negatively correlated with running distance (r = −0.84, p = 0.03). Blood La levels at exhaustion offer a cost‐effective method to confirm exhaustion criteria and enhance the reliability of exercise tests. La at rest may not reflect CHF severity or exercise adaptation but correlates better with exercise capacity in CHF.